Platelet-Lymphocyte Ratio and Neutrophil-Lymphocyte Ratio as Early Mortality Predictors for Patients with End-Stage Chronic Liver Disease - Syifa Mustika; Affa Kiysa Waafi (The Indonesian Society for Digestive Endoscopy, 2022)
Background: Chronic liver disease (CLD) often results in fatal complications. Child-Turcotte-Pugh (CTP) score is the earliest predictor of mortality but the Model for End-Stage Liver Disease (MELD) score is more objective. Studies showed platelet-lymphocyte ratio (PLR) and neutrophil-lymphocyte ratio (NLR) could become mortality predictors for chronic liver disease. We aimed to investigate NLR and PLR as early mortality predictors for CLD, in comparison with CTP and MELD scores. Method: This was a retrospective observational cohort study. We recruited patients with CLD (liver cirrhosis and hepatocellular carcinoma), from Saiful Anwar Hospital, Indonesia. Data regarding PLR, NLR, CTP, and MELD scores were obtained from the medical records. Participants were followed for 30 days to determine survival. Results: Ninety patients were recruited in the study. There were 31 deaths (34.4%) in 30 days. Mortality was higher in HCC patients than liver cirrhosis. Although NLR had similar sensitivity with CTP (51.6%), neither PLR (p 0.956) nor NLR (p 0.087) could significantly better predict mortality than CTP (p 0.001) or MELD scores (p 0.002). In opposite to PLR, NLR had a positive correlation with MELD and CTP scores. Conclusion: On the contrary to the PLR, the NLR positively correlated with the severity of the disease, NLR had the potential as a predictor of early mortality for patients with chronic liver disease as compared to CTP and MELD scores. But PLR could not substitute both CTP and MELD scores.